Les pentes raides de la vallée de la rivière du nord – Étude de versants-échantillons - Lasserre, Jean-Claude (Cahiers de géographie du Québec, 1965)
The author recently made a detailed investigation of the talus accumulations which mantle the steep slopes of the valley of the rivière du Nord, in the Laurentide hills, 45 miles north of Montréal, Québec. In postglacial times the lower section of the valley was occupied by an arm of the Champlain sea, and thick deposits of sand and clay were laid down in this estuary. The writer describes the various types of contacts which exist between the Champlain sea deposits and the talus accumulations — for example, certain talus slopes were completely covered by marine sediments and remain « fossilized  » ; others have been stripped of their cover of unconsolidated materials and are consequently described as « exhumed  ». The writer has also attempted to distinguish between those talus accumulations which antedate the Champlain incursion and those which postdate it. Most of the talus slopes appear to have formed immediately prior to or during the Champlain period, but a few have developed, at least in part, since that time. Frost-shattering (gelifraction) is the principal process contributing to the formation of these talus accumulations at the present time, although landslides also play an important role. The writer wonders whether these talus slopes of the valley of the rivière du Nord should not be classified as periglacial landforms.